Epidemiological Profile of Crimean-Congo Hemorrhagic Fever in Thi-Qar Province, Iraq: A Three-Year Retrospective Analysis - Othman, Rana Ali; Falih, Ramiz T.; Atiyah, Ammar Mohammed; Mostafa, Fatma M. (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Crimean-Congo hemorrhagic fever (CCHF) is a severe disease. It is most commonly spread by the bite of an infected tick of the Hyalomma genus, or by direct contact with blood and bodily fluids of an infected person or other animals. The current study aimed to determine the prevalence of hemorrhagic fever cases during 3 years in Thi-Qar province and also study demographic factors. Methods: Data were collected from the records of the Statistics Unit at the Public Health Laboratory. The epidemiological data were collected from the beginning of December 2023 to the end of March 2024. Results: A total of 319 cases, which included 184 (57.7%) males and 135 (42.3%) females. The number of people recovered was 256 (80.3%), whereas the deceased cases recorded were 63 (19.7%). The highest rate of infection appeared in the age group of 20–39 years (41.4%), and the lowest proportion (11.0%) was in the ≥60 years age group. According to occupation, housewives were the highest proportion (37.9%). Total annual infections were recorded 4.7%, 50.8% and 44.5%, respectively. Conclusion: The study highlighted the epidemiological features. The results indicate patterns in the distribution of cases across demographic and geographic variables. We conclude from the current study that occupational and home exposure, especially among housewives, are among the most common cases of hemorrhagic fever.